(3GYJbGOGJ cafs
(3ChdgG (B:s
(3Ef adGf jTgOGf dG Edg EdG Gddg hMOg dGTQjc dg hGf eMeO YHOg hQShdg hGf YdjkG hdjg s
(3BNQgG (B:s
(3jSHM Gddg hMOg ai fGMjI HCUfGa eNJdaI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , JGeI s
Keywords: (3GdeLGejYs